Clinical outcomes of an intelligent pressure-controlled disposable ureteroscope for Laser lithotripsy in renal stone surgery: a retrospective matched cohort study - Lv, Zhong; Jiao, Zhimin; Shi, Honglei; Yuan, Xiaoliang; Wu, Tingchun; Wu, Haoran (Frontiers in Surgery, 2025)
PurposeTo compare the clinical application efficacy of an intelligent pressure-controlled disposable ureteroscope vs. a conventional disposable ureteroscope with laser lithotripsy in upper urinary tract calculi surgeries.MethodsThe experimental group (n = 70) underwent surgery using an intelligent pressure-controlled disposable ureteroscope with laser lithotripsy, while the control group (n = 70) underwent traditional disposable ureteroscope Holmium laser lithotripsy. The perioperative conditions of patients in both groups were observed, including average surgical time, postoperative hemoglobin loss, average hospital stay, renal pelvis pressure, blood urea nitrogen (BUN), serum creatinine (Scr), platelets (PLT), infection and inflammation indicators, initial stone clearance rate, and total stone clearance rate. The occurrence rate of postoperative complications in both groups was assessed using the Clavien-Dindo classification, and the differences in complication rates between the groups were compared.ResultsThe experimental group had a longer surgical time, but a shorter hospital stay and lower renal pelvis pressure. Inflammatory markers including WBC, CRP, and PCT were significantly lower postoperatively in the experimental group. Initial stone clearance and total clearance rates were also higher. The overall complication rate was significantly lower in the experimental groupConclusionsThe use of an intelligent pressure-controlled disposable ureteroscope with laser lithotripsy for upper urinary tract surgeries can effectively reduce postoperative inflammation indicators, decrease average hospital stay and renal pelvis pressure, and improve the initial and total stone clearance rates.